Vice-principals as leaders: Role ambiguity and role conflicts faced by vice-principals in Singapore. (May 2023) - Ho, Jeanne; Shaari, Imran; Kang, Trivina
This article examines what vice-principals in Singapore experience as constraints to their leadership practice, and how they deal with these constraints, cognisant that role misalignment for vice-principals presents barriers to schools achieving optimal effectiveness. This qualitative study seeks to hear the voices of vice-principals, to uncover the contextual richness of their experiences through interviews with 28 vice-principals. Coding involved a mix of codes from the literature and from the interviews, with member checking of the findings. Vice-principals in Singapore face two main constraints: role ambiguity and role conflicts. These are mainly a structural issue, given the dual expectations of vice-principals to support their principals and to lead. The problems are heightened when there are clashes of values, with vice-principals conflicted between two sources of authority: administrative and professional. Framing the constraints faced by vice-principals under role ambiguity and role conflicts raises these constraints to a theoretical and organisational level. The study proposes a link between the concepts of role ambiguity and role boundaries and illustrates how role ambiguity and conflicts can be disempowering. However, the study also shows that ambiguity need not always be a constraint but can be positive under some conditions.